Critical pedagogy as a means to develop the moral autonomy - Escobar Galo, Juan Pablo (2016)
The main objective of this paper is to present contemporary studies and proposals on the emergence of moral conscience and the exercise of moral autonomy and analyze whether the educational approach of Paulo Freire favor or not the exercise of freedom and autonomy settings moral. To understand the development of moral autonomy is necessary to explain the principles of birth of the moral conscience of Jean Piaget, the processes of moral development of Lawrence Kohlberg and the communicative action and moral development from the perspective of Jürgen Habermas. Freire's critical pedagogy focuses on three areas: awareness of the subjects (reading of the world) against reality, the exercise of freedom from educational activities and the generation of critical thinking from the individual to the community, which involves understanding the story (personal and community) as a possibility and not as determination.